Lost in transition? Drivers and barriers in the eco-innovation road to the circular economy - Jesus. A.; Mendonça, S. (Ecological Economics, 2018)
Understanding which drivers and barriers exist in the development of a Circular Economy (CE) is a relevant and timely endeavour. The aim of this paper is to contribute to this debate by analysing evidence regarding the different factors helping and hampering the development of a CE. Specifically, this paper focuses on the eco-innovation (EI) pathway towards a CE, and tries to coordinate available but fragmented findings regarding how “transformative innovation” can foster this transition while removing obstacles to sustainability. Drawing upon a new corpus of both academic and non-academic literature, this work offers a framework for analysis, as well as an evidence-based survey of the challenges and potential for a green structural transformation of the economy. In line with this “transformation turn” an innovation systems’ view may provide an appropriate perspective for understanding the transition to a CE. Ultimately, the paper aims to contribute to the design of policy guidelines and organisational strategies.